2021
DOI: 10.1007/s10815-021-02356-1
|View full text |Cite
|
Sign up to set email alerts
|

MUM-1 immunohistochemistry has high accuracy and reliability in the diagnosis of chronic endometritis: a multi-centre comparative study with CD-138 immunostaining

Abstract: Purpose The current gold standard for chronic endometritis (CE) diagnosis is immunohistochemistry (IHC) for CD-138. However, IHC for CD-138 is not exempt from diagnostic limitations. The aim of our study was to evaluate the reliability and accuracy of MUM-1 IHC, as compared with CD-138. Methods This is a multi-centre, retrospective, observational study, which included three tertiary hysteroscopic centres in university teaching hospitals. One hundred ninety-three consecutive women of reproductive age were refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 34 publications
1
21
0
3
Order By: Relevance
“…This prospective, observational, analytical, cross-sectional study has been conducted on one hundred fifty women, who were affected by infertility and one or more unexplained implantation failures. The final results are as follow: Table ( Table (7) shows that, there is a highly significant relationship between residence and number of previous unexplained implantation failure, as 50/66 of the rural areas cases experienced RIF (P value 0.0012) Table (10) shows that, 89.3% of cases were without other abnormal findings during hysteroscopy as endometrial polyp, fine adhesions, or cervical stenosis.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…This prospective, observational, analytical, cross-sectional study has been conducted on one hundred fifty women, who were affected by infertility and one or more unexplained implantation failures. The final results are as follow: Table ( Table (7) shows that, there is a highly significant relationship between residence and number of previous unexplained implantation failure, as 50/66 of the rural areas cases experienced RIF (P value 0.0012) Table (10) shows that, 89.3% of cases were without other abnormal findings during hysteroscopy as endometrial polyp, fine adhesions, or cervical stenosis.…”
Section: Resultsmentioning
confidence: 96%
“…In contrast, Kasius and coworkers [7] reported that the clinical implication of chronic endometritis seems minimal since they diagnosed this condition in 2% of asymptomatic infertile patients with a normal transvaginal ultrasound examination (TVS). The same author reported that the reproductive outcome at ICSI cycles was not negatively affected by chronic endometritis and that the low prevalence and unknown clinical significance of it warrants further study [7,12]. The aim of the study was to evaluate the effects of chronic endometritis on implantation failure at ICSI through its prevalence at hysteroscopy and histology, in a population of women who experienced implantation failure at ICSI.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…[5][6][7] Immunohistochemistry is a commonly used ancillary test in pathology, and immunostains such as CD138 and MUM1 have been shown to be helpful to identify endometrial stromal PCs. 23,24 Although multiple sources suggest additional morphologic findings, such as spindling of the stroma and endometrium that is hard to date, as diagnostic features of CE, 2,6,16 the minimal diagnostic criteria for CE are controversial. 3,7,23 A substantial number of articles in the fertility literature use a threshold of 1 or more PCs identified using CD138 IHC as the minimal diagnostic criterion for CE.…”
Section: Diagnostic Considerationsmentioning
confidence: 99%